Systematic Engineering of Uniform, Highly Efficient, Targeted and Shielded Viral‐Mimetic Nanoparticles. Issue 16 (7th March 2013) - Karjoo, Zahra; McCarthy, Helen O.; Patel, Parin; Nouri, Faranak Salman; Hatefi, Arash
Abstract In the past decades, numerous types of nanomedicines have been developed for the efficient and safe delivery of nucleic acid‐based drugs for cancer therapy. Given that the destination sites for nucleic acid‐based drugs are inside cancer cells, delivery systems need to be both targeted and shielded in order to overcome the extracellular and intracellular barriers. One of the major obstacles that has hindered the translation of nanotechnology‐based gene‐delivery systems into the clinic has been the complexity of the design and assembly processes, resulting in non‐uniform nanocarriers with unpredictable surface properties and efficiencies. Consequently, no product has reached the clinic yet. In order to address this shortcoming, a multifunctional targeted biopolymer is genetically engineered in one step, eliminating the need for multiple chemical conjugations. Then, by systematic modulation of the ratios of the targeted recombinant vector to PEGylated peptides of different sizes, a library of targeted–shielded viral‐mimetic nanoparticles (VMNs) with diverse surface properties are assembled. Through the use of physicochemical and biological assays, targeted–shielded VMNs with remarkably high transfection efficiencies (>95%) are screened. In addition, the batch‐to‐batch variability of the assembled targeted–shielded VMNs in terms of uniformity and efficiency is examined and, in both cases, the coefficient of variation is calculated to be below 20%, indicating a highly reproducible and uniform system. These results provide design parameters for engineering uniform, targeted–shielded VMNs with very high cell transfection rates that exhibit the important characteristics for in vivo translation. These design parameters and principles could be used to tailor‐make and assemble targeted–shielded VMNs that could deliver any nucleic acid payload to any mammalian cell type.